Morphological Identification of Balinese Caulerpa Seaweeds - Dewi, Ni Kadek Emi Sintha; Wirawan, I Gede Putu; Suada, I Ketut (Jurnal Biologi Tropis, 2024)
Bulung boni and bulung anggur are species of Caulerpa seaweeds commonly found along the coastline of Serangan Island, Bali. Although these species have been widely utilized in various ways, formal species identification of these two macroalgae in Bali had not been conducted prior to this study. This research aims to characterize the morphological structures of bulung boni and bulung anggur through detailed morphological examination. Identification keys and previous studies were used to assist in the morphological identification process. The findings revealed that bulung boni shares morphological characteristics with Caulerpa cylindracea, while bulung anggur is morphologically comparable to Caulerpa macrophysa. These results provide valuable insights into the species composition of seaweeds in the region and contribute to a better understanding of local biodiversity.